Comparing United States and European Union Approaches to Engagement with Asia - Hang, Nguyen Thi Thuy (Malaysian Journal of International Relations, 2016)
The United States (U.S.) and the European Union (EU) have attempted to project themselves as important actors in Asia. They made official announcements of shifting more attention to Asia in 2011-2012. This paper aims to examine and compare their approaches to engagement with Asia and put forth policy recommendations for them to engage with Asia effectively. As their engagement with Asia is becoming multidimensional, this paper places an emphasis on security, economics and diplomacy. Drawing mainly on scholar analysis and official documents regarding the U.S.’ and EU’s engagement wit Asia, this paper has found out there that there are both similarities and differences in the U.S. and the EU approaches engagement with Asia. It also highlights the core ideas underpinned the U.S. and the EU engagement with Asia.